2012
DOI: 10.1007/s10546-012-9735-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards Reconciling the Large-Scale Structure of Turbulent Boundary Layers in the Atmosphere and Laboratory

Abstract: A collaborative experimental effort employing the minimally perturbed atmospheric surface-layer flow over the salt playa of western Utah has enabled us to map coherence in turbulent boundary layers at very high Reynolds numbers, Re τ ∼ O(10 6 ). It is found that the large-scale coherence noted in the logarithmic region of laboratory-scale boundary layers are also present in the very high Reynolds number atmospheric surface layer (ASL). In the ASL these features tend to scale on outer variables (approaching the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
248
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(293 citation statements)
references
References 95 publications
(198 reference statements)
44
248
1
Order By: Relevance
“…In order to elucidate the possible origin of the high-speed region observed in Figure 17a,c, one can notice that the flow in both cases is generally directed from the high-speed region to the low-speed one at around turbine hub-height level, and it gradually changes direction with increasing height. This is similar to the flow motion between well-known high-and low-speed streaks, known as very-large-scale motions (VLSMs), in turbulent boundary layers [45][46][47]. In addition, the size of high-speed regions shown in Figure 17a,c is in the same order of magnitude as the values reported in the literature for the size of VLSMs in boundary-layer flows (e.g., [45]).…”
Section: Wake Dynamics: Meandering Motionssupporting
confidence: 83%
“…In order to elucidate the possible origin of the high-speed region observed in Figure 17a,c, one can notice that the flow in both cases is generally directed from the high-speed region to the low-speed one at around turbine hub-height level, and it gradually changes direction with increasing height. This is similar to the flow motion between well-known high-and low-speed streaks, known as very-large-scale motions (VLSMs), in turbulent boundary layers [45][46][47]. In addition, the size of high-speed regions shown in Figure 17a,c is in the same order of magnitude as the values reported in the literature for the size of VLSMs in boundary-layer flows (e.g., [45]).…”
Section: Wake Dynamics: Meandering Motionssupporting
confidence: 83%
“…Support for this also comes from atmospheric surface layer and laboratory measurements as described in Hambleton et al (2006) and Hutchins et al (2012), as shown in Fig. 6, where simultaneous x − y and x − z plane three-component velocity measurements reveal signatures entirely consistent with the superstructure events consisting of an organized array of packet structures.…”
Section: Large-scale Motions and Very Large-scale Superstructuresmentioning
confidence: 63%
“…Here, the black isocontours show swirl strength, indicating the corresponding location of vortical structures with the low-speed (blue) and high-speed (red) regions. After Marusic and Adrian (2013) Figure 6 Top panel: instantaneous velocity fluctuations in the streamwise-wall-normal (x-y) plane and instantaneous streamwise velocity fluctuations in the streamwise/spanwise (x-y) planes for data from laboratory PIV (Hambleton et al 2006) and for the atmospheric surface layer using an arrays of sonic anemometers (Hutchins et al 2012). High-positive w regions are indicated by red, while blue denotes highly negative w regions.…”
Section: Large-scale Motions and Very Large-scale Superstructuresmentioning
confidence: 99%
“…This figure has reference curves corresponding to a constant physical inclination angle θ, which were constructed via τ U ∞ /δ = (z w − z)/ tan(θ )/δ. Typically, angles of θ ≈ 16 • have been reported for the u component of velocity [5]. Figure 3b shows that the shift is only weakly dependent on scale, and so the large scales are said to be non-dispersive.…”
Section: ) and U(z T)mentioning
confidence: 98%